The Caliphate as a Foundation for Socio-Political Stability: A Theoretical Reconstruction of Authority and Governance In Islamic Administration - Safitri Agustina; Erlian Eka Damayanti; Muhammad Akmansyah; Zulhanan Zulhanan; Fachrul Ghazi (Assyfa Journal of Multidisciplinary Education, 2026)
This study aims to reconstruct the concept of caliphate as a normative governance paradigm that functions as the foundation of socio-political stability within the framework of Islamic political thought. This study also examines the epistemological interaction between the concept of caliphate and modern state theories. Methods: This study employed a qualitative-interpretative approach based on doctrinal analysis. Primary data were obtained from normative Islamic political texts, while secondary data were derived from classical and contemporary literature related to Islamic governance, maqāṣid al-sharī'ah, political legitimacy, and modern governance theories. The analysis was conducted through conceptual classification, maqāṣid synthesis, and comparative epistemological dialogue. Results: The study found that the caliphate is conceptually positioned as a normative authority that maintains legal unity, multidimensional stability, and moral legitimacy. Stability within the caliphate framework is not limited to political order but includes spiritual, social, economic, and legal stability. Furthermore, political authority in Islam is fundamentally based on the concept of amanah (trusteeship), rather than absolute sovereignty. This study offers a reconstruction of the caliphate as a moral governance paradigm grounded in maqāṣid al-sharī'ah and provides a dialogical framework between Islamic political theory and modern governance discourse.